2018
DOI: 10.20886/jphh.2018.36.1.59-65
|View full text |Cite
|
Sign up to set email alerts
|

Komposisi Kimia Dan Keawetan Alami Delapan Jenis Kayu Di Bawah Naungan

Abstract: Timber utilization is mostly affected by wood chemical composition and its natural durability in certain condition. This paper studies chemical composition and under shade natural durability of eight wood species originated from Banten and West Java Provinces. Chemical composition was tested based on Norman and Jenkins' methods, SNI 14-0492-1989 and SNI 14-1032-1989 and the wood natural durability test was conducted outdoor under the shade. Result shows that in general wood chemical composition of eight wood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
(7 reference statements)
0
4
0
2
Order By: Relevance
“…The lignin content before being treated was in the high category, which was more than 33%, but after being immersed in KMnO4 2% and NaOH 5%, the lignin level was changed to the low category which is less than 18% [23]. Research using Borassus fruit fiber treated with NaOH also showed a reduction in lignin levels [16].…”
Section: Resultsmentioning
confidence: 95%
“…The lignin content before being treated was in the high category, which was more than 33%, but after being immersed in KMnO4 2% and NaOH 5%, the lignin level was changed to the low category which is less than 18% [23]. Research using Borassus fruit fiber treated with NaOH also showed a reduction in lignin levels [16].…”
Section: Resultsmentioning
confidence: 95%
“…The high cellulose content influences termite attacks on wood in wood. Cellulose and lignin strengthen cell walls [23,24,25]. A mixture of cellulose with lignin increases its high preference for termites.…”
Section: Termite Attacks On Living Plantsmentioning
confidence: 99%
“…In general, wood consists of chemicals such as carbohydrates, cellulose, lignin, and extractives. One of the substances that determine the durability of wood is the extractive substance (Wibisono et al, 2018).…”
Section: Wood-producing Plantsmentioning
confidence: 99%